2018
DOI: 10.1002/ps.5080
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide hormesis can act as a driver of resistance evolution in weeds – PSII‐target site resistance in Chenopodium album L. as a case study

Abstract: Agronomically relevant doses of metamitron induced considerable hormesis in a PSII-TSR C. album genotype leading to enhanced relative fitness through reproductive maturity. This increase in relative fitness suggests an impact on resistance selection and can compensate for the oft-reported fitness costs of the mutation studied. Field rates of herbicides can, thus, not only select for resistant plants, but also enhance their reproductive fitness. The finding that herbicide hormesis can be eco-evolutionary import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
(133 reference statements)
3
29
0
Order By: Relevance
“…Because hormesis is considered a general and widespread phenomenon, the reproduction of resistant weed (sub)populations may be similarly promoted. The results showing the promotion of reproductive traits in hormetically enhanced resistant weed plants by up to 15–32% under practical herbicide application rates support this hypothesis . An up to 32% higher yield of seeds carrying particular resistance genes clearly indicates that these resistance genes may rapidly accumulate via selective hormesis.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Because hormesis is considered a general and widespread phenomenon, the reproduction of resistant weed (sub)populations may be similarly promoted. The results showing the promotion of reproductive traits in hormetically enhanced resistant weed plants by up to 15–32% under practical herbicide application rates support this hypothesis . An up to 32% higher yield of seeds carrying particular resistance genes clearly indicates that these resistance genes may rapidly accumulate via selective hormesis.…”
Section: Discussionsupporting
confidence: 81%
“…The results showing the promotion of reproductive traits in hormetically enhanced resistant weed plants by up to 15-32% under practical herbicide application rates support this hypothesis. 12 An up to 32% higher yield of seeds carrying particular resistance genes clearly indicates that these resistance genes may rapidly accumulate via selective hormesis. Therefore, selective hormesis may not only accelerate the evolution of resistance but also influence the type of resistance genes being enriched.…”
Section: Cycloxydimmentioning
confidence: 99%
See 1 more Smart Citation
“…ha −1 for seed number (Fig. )], it is indicated that if a preconditioning dose is located within the increasing part of the parental hormetic curve (< M F0 ), offspring priming acts more on sensitivity reduction. Higher preconditioning doses located within the decreasing part of the parental hormetic curve (> M F0 ) seem to prime instead for an enhanced ability to increase plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, an array of research programs has demonstrated that low doses of stresses stimulate not only plants but also microorganisms, insects and other potential agricultural pests [ 17 , 18 , 19 ]. This stimulation often has inter- and intra-generational effects and acts as a hormetic preconditioning vehicle, which can enhance the tolerance of pests to pesticides and potentially lead to intra-generationally attained resistance [ 17 , 19 ]. Hence, low-doses of pesticides that protect plants against O 3 -induced phytotoxicity may be that low to finally stimulate pests populations outbreak, leading to pesticides tolerance or resistance in the same or subsequent generations.…”
Section: Introductionmentioning
confidence: 99%